Operational modal analysis and Bayesian model updating of a standing seam metal roofing system. (21st May 2019) - Hu, Jun; Lam, Paul Heung-Fai; Chung, Kwok-Fai
Clip detachment is found to be a common failure mode for metal roofs. It leads to the stiffness reduction at some supports of the metal roof and alter its dynamic characteristics. Therefore, it is possible to detect the damage of clips by monitoring the modal properties. To assess the dynamic properties of metal roofs, part of a full-scale standing seam metal roof was constructed on a supporting steel frame in the laboratory. Modal parameters were identified from the measured acceleration responses using frequency domain decomposition method (FDD). The finite element model of the system was developed, and the clip stiffness was estimated by Markov chain Monte Carlo (MCMC)-based Bayesian model updating method. Both the modal identification and model updating results are reported in detail. The results presented in this paper are valuable and important for the development of a structural health monitoring system for metal roofing system.